An electron beam induced study in fluorine doped ZnO nanostructures for optical filtering and frequency conversion application. (July 2019) - Antony, Albin; Poornesh, P.; Ozga, K.; Rakus, P.; Wojciechowski, A.; Kityk, I.V.; Sanjeev, Ganesh; Petwal, Vikash Chandra; Verma, Vijay Pal; Dwivedi, Jishnu
Highlights: FZO nanostructures were treated with 8 MeV e-beam line at dosages 0 to 20 kGy. XPS conveys that e-beam treatment suppresses the generation of defects in FZO. Non radiative recombination dominates over radiative recombinations in FZO. Nonlinear scattering mechanism becomes dominant due to photo bleaching effect. Abstract: Influence of high energy electron beam treatment on fluorine doped ZnO (FZO) nanostructures and its role in modifying structural, optical, morphological and nonlinear optical properties was studied. FZO nanostructures were grown with different fluorine concentration using an air assisted chemical spray pyrolysis technique. The prepared nanostructures were treated with 8 MeV electron beam line at pre-determined dosages (5 kGy. 10 kGy, 15 kGy and 20 kGy). Compositional and chemical state analysis of FZO films were analyzed by x-ray photoelectron spectroscopy (XPS). The XPS analysis conveys that the percentage area ratio of O1s core level spectra which attributes to oxygen vacancy defects are reduced from 28.9% to 13.7% which endorses a fact that e-beam treatment suppresses the generation of oxygen related defects. The glancing angle X-ray diffraction (GAXRD) study confirms that the deposited films exhibit a single phase which point towards the higher order structural stability and phase purity of FZO nanostructures in intense radiation environment. The ambient temperature PL spectra show quenching of radiative defect centers upon electron beam irradiation which infers that non radiative recombination predominates the radiative recombination in the nanostructures upon e-beam treatment. Open aperture Z-scan analysis shows a magnitude of nonlinear absorption coefficient βeff in the order of 10 −1  esu. Enhanced third harmonic generation signal (THG) shown by the films due to photoexcitation and relaxation process endorses the credibility of the grown films for application as UV light emitters.